Copper Levels in Patients with Unexplained Dysplastic Cytopenia - Butcher, Dominic (Biol Trace Elem Res, 2020)
Copper deficiency can produce changes mimicking myelodysplasia, but its prevalence among haematology patients is unknown. This study evaluates the prevalence of deficiency in a population of patients with unexplained cytopenia(s) and dysplasia. Of 17 patients recruited, only one was found to have a low copper level. This is the first study evaluating hypocupremia in patients with isolated haematological manifestations. Our results suggest that copper deficiency is uncommon in this population, and the routine measurement of copper seems unlikely to be cost-effective. We recommend a risk-assessed approach to testing based on the identification of risk factors and of signs suggestive of deficiency. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12011-020-02203-x) contains supplementary material, which is available to authorized users.